2007
DOI: 10.1038/sj.bjc.6604009
|View full text |Cite
|
Sign up to set email alerts
|

PTEN loss of expression predicts cetuximab efficacy in metastatic colorectal cancer patients

Abstract: To evaluate whether the epidermal growth factor receptor (EGFR), K-Ras and PTEN, all members of the EGFR signalling pathway, may affect the clinical response in cetuximab-treated metastatic colorectal cancer (mCRC) patients. Twenty-seven cetuximab-treated mCRC patients were evaluated for drug response and investigated for EGFR protein expression and gene status, K-Ras mutational status and PTEN protein expression. Ten patients achieved a partial response (PR) to cetuximab-based therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
372
4
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 484 publications
(415 citation statements)
references
References 31 publications
25
372
4
10
Order By: Relevance
“…Cell lines deficient in PTEN expression are more resistant to cetuximab in vitro than those with normal PTEN expression [46]. The loss of PTEN protein expression negatively predicts efficacy of cetuximab therapy in patients with metastatic colorectal cancer [50]. In this study, 63% (10/16) of patients with tumors that showed normal PTEN expression were able to achieve a partial response whereas no response was documented in 11 patients with tumors that lacked PTEN expression [50].…”
Section: Biomarkers In Colorectal Cancermentioning
confidence: 60%
“…Cell lines deficient in PTEN expression are more resistant to cetuximab in vitro than those with normal PTEN expression [46]. The loss of PTEN protein expression negatively predicts efficacy of cetuximab therapy in patients with metastatic colorectal cancer [50]. In this study, 63% (10/16) of patients with tumors that showed normal PTEN expression were able to achieve a partial response whereas no response was documented in 11 patients with tumors that lacked PTEN expression [50].…”
Section: Biomarkers In Colorectal Cancermentioning
confidence: 60%
“…First, we collected individual data on the ORR from 7 studies 6,13,14,18-21 that did not perform a comparison between patients with the KRAS p.G13D mutation and KRAS codon 12 mutations, which significantly increased the statistical power of the analysis. Second, except for 2 abstracts, 16,17 all fulltext studies 6,[13][14][15][18][19][20][21] were of high quality, with an average NOS score of 7. Third, no heterogeneity was observed in any comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab was received as first-line treatment in 1 study 17 and as firstline or subsequent treatment in 9 studies. 6,[13][14][15][16][18][19][20][21] Patients received cetuximab plus chemotherapy in 5 studies 14,16,17,19,21 and cetuximab-based treatment (cetuximab monotherapy or cetuximab plus chemotherapy) in the remaining 5 studies. 6,13,15,18,20 Quality-Assessment Results…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations